2021
DOI: 10.3390/antibiotics10070872
|View full text |Cite
|
Sign up to set email alerts
|

MCR Expression Conferring Varied Fitness Costs on Host Bacteria and Affecting Bacteria Virulence

Abstract: Since the first report of the plasmid-mediated, colistin-resistant gene, mcr-1, nine mcr genes and their subvariants have been identified. The spreading scope of mcr-1~10 varies greatly, suggesting that mcr-1~10 may have different evolutionary advantages. Depending on MCR family phylogeny, mcr-6 is highly similar to mcr-1 and -2, and mcr-7~10 are highly similar to mcr-3 and -4. We compared the expression effects of MCR-1~5 on bacteria of common physiological background. The MCR-1-expressing strain showed bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…A possible explanation may reside in a recent study analysing the fitness cost of bacteria carrying mcr‐1 to mcr‐5 , where the growth of mcr‐4 and mcr‐5 strains in broth culture was significantly inhibited in the log phase when colistin was added in the medium (Li et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation may reside in a recent study analysing the fitness cost of bacteria carrying mcr‐1 to mcr‐5 , where the growth of mcr‐4 and mcr‐5 strains in broth culture was significantly inhibited in the log phase when colistin was added in the medium (Li et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first experiment using selective media to isolate colistin-resistant strains from meat samples, so it is difficult to state whether this difference in performance is due to the medium, the gene (mcr-4) or the bacteria (Salmonella). A possible explanation may reside in a recent study analysing the fitness cost of bacteria carrying mcr-1 to mcr-5, where the growth of mcr-4 and mcr-5 strains in broth culture was significantly inhibited in the log phase when colistin was added in the medium (Li et al 2021).…”
Section: Performance Of the Selective Media To Isolate Mcrpositive Ba...mentioning
confidence: 99%
“…Antibiotic resistance mediated by acquiring mobile elements, including plasmids, imposes fitness costs on the bacterial host. In the absence of antibiotic pressure, sensitive strains can easily replace the resistant strains having an extra burden [ 86 , 87 ]. A recent study revealed that the expression of MCR-1 and MCR-3 has fitness cost on the first 50 generations of bacteria and that these genes and plasmids can persist over time, suggesting that the burden costs are alleviated through compensatory mutations [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study of the impact of diverse plasmids, harbouring COL resistance gene mcr-1 on host fitness, demonstrated that the IncI2, IncHI2 and IncX4 plasmid-carrying mcr-1 genes are stable and hardly affect bacterial growth, suggesting that most reported mcr-1 -plasmids belong primarily to these types [ 88 , 89 ]. Increased fitness or co-selection by other antimicrobials might contribute to the further dissemination of mcr-1 –positive plasmids [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid stability of transconjugants was determined based on a previous study (Li et al, 2021b). Ten microliters of overnight seed cultures of the strains was inoculated into 10 ml antibiotic-free LB medium (1:1,000 ratio).…”
Section: Plasmid Stability Assaymentioning
confidence: 99%